Infecção experimental de bezerros com isolados brasileiros de pestivírus HoBi-like - Jardim, José Conrado dos Santos (2018)
HoBi-like viruses belong to a yet unclassified group of bovine pestiviruses of cattle, originally identified in commercial fetal bovine serum (FBS) of Brazilian origin and, subsequently, isolated from FBS and from sick animals in several countries. Although frequently isolated from overt, severe disease, most HoBi-like isolates do not reproduce marked clinical signs when inoculated experimentally. In this study, the experimental infection of calves with two Brazilian isolates of HoBi-like pestivirus was carried out. Four to six months-old, seronegative calves inoculated by the intranasal route (IN) with isolate SV757/15 presented viremia between days 4 and 12 post-infection (pi) and excreted virus in nasal secretions until the day 12 pi. Clinically, the inoculated animals presented transient hyperthermia (days 4 to 8 pi) and lymphopenia between days 4 and 8 pi. In a second experiment, calves inoculated with isolate SV478/07 showed apathy, anorexia, mild respiratory signs and pasty diarrhea on the days following inoculation. These animals developed hyperthermia (day 4 to 9 pi), lymphopenia (day 4 to 7pi), viremia between days 2 and 9 and virus excreted in nasal secretions up to day 14 pi. Both groups seroconverted to the inoculated viruses, developing neutralizing antibody titers between 40 and 1280 on day 30 pi. These results confirm and extend previous findings showing that infections of susceptible cattle with HoBi-like pestiviruses are predominantly subclinical or accompanied by mild clinical signs. Nonetheless, these results also indicate the existence of differences in virulence among field isolates.